Ensuring Relay Protection Device Reliability by Setting Value and Time Delay Verification (10Kv Motor Differential Current Protection) - Kamal, Ahmad Ilham; Dona, Nur Rahma (Setrum : Sistem Kendali-Tenaga-elektronika-telekomunikasi-komputer, 2024)
Protection relay devices are very important in the electrical system where they act as voltage breakers when there is a disturbance in the electrical system so that electrical equipment and those connected to it are not damaged. Based on the IEC 60255 standard, protection relay devices are required to be reliable, fast, and selective so that the electrical system is protected from disturbances and works properly without miss-operation. The standard tolerance for the verification value deviation is not more than 5% of the setting value, this refers to the IEC 60255 standard. This journal explains the testing of setting valuesand time delays on protection relay devices that focus on differential current protection. The results of this test can be concluded whether the protection relay is still suitable for use or not with a standard tolerance deviation of ≤5%.